2023
DOI: 10.1038/s41467-023-37919-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic self-organisation and pattern formation by magnon-polarons

Abstract: Magnetic materials play a vital role in energy-efficient data storage technologies, combining very fast switching with long-term retention of information. However, it has been shown that, at very short time scales, magnetisation dynamics become chaotic due to internal instabilities, resulting in incoherent spin-wave excitations that ultimately destroy magnetic ordering. Here, contrary to expectations, we show that such chaos gives rise to a periodic pattern of reversed magnetic domains, with a feature size far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Note that only two magnetic domains are observed, even though the sample exhibits a four-fold in-plane anisotropy. We find that this pattern is rather typical when the thin film is exposed to a macropulse, whereas a single micropulse generally gives rise to four magnetic domains [10]. We speculate that this drastically different pattern stems from the slower processes of domain formation that occur across the time scale of microseconds.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Note that only two magnetic domains are observed, even though the sample exhibits a four-fold in-plane anisotropy. We find that this pattern is rather typical when the thin film is exposed to a macropulse, whereas a single micropulse generally gives rise to four magnetic domains [10]. We speculate that this drastically different pattern stems from the slower processes of domain formation that occur across the time scale of microseconds.…”
mentioning
confidence: 74%
“…Phononic switching of magnetization-the process through which magnetization is solely reversed by the excitation of optical phonons at resonance-poses an intriguing and somewhat counter-intuitive mechanism for magnetic reversal [8,10]. The thriving research field of non-linear phononics has revealed that infrared-active transverse optical (TO) phonon modes, when driven at resonance to high amplitude [11,12], can give rise to a wealth of transient effects and functionalities such as promoting superconductivity to room temperature or transforming insulators into metals [13,14].…”
mentioning
confidence: 99%